The execution of digital first editorial strategy in South Africa : the case of Netwerk24, Beeld, Die Burger and Volksblad - Vermeulen, Marguerite (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.